Colchicine therapy in cardiovascular medicine: A literature review - Jennifer Trube; Michael Sabina; Aqeel Khanani; Kayla Hernandez; Zoya Khan; Anas Bizanti (American Heart Journal Plus)
Introduction: Inflammation is a key risk factor in cardiovascular diseases, such as atherosclerosis, and has been linked to increased mortality following myocardial infarction. While inflammation promotes tissue repair, sustained inflammation can drive adverse cardiac remodeling, fibrosis, and impaired contractility, resulting in poorer outcomes. This maladaptive remodeling, compounded by oxidative stress, also predisposes patients to cardiovascular diseases. Colchicine has shown anti-inflammatory benefits in cardiovascular disease, but its role in individual diseases remains unclear. This literature review seeks to understand and evaluate the clinical trials evaluating colchicine in cardiovascular treatment. Methods: A literature search identified randomized controlled trials (RCTs) evaluating colchicine in cardiovascular disease including coronary artery disease, post-myocardial infarction treatment, atrial fibrillation, heart failure, and stroke. Conclusions: Colchicine has been studied across many cardiovascular conditions including atrial fibrillation (AF), coronary artery disease (CAD), post-myocardial infarction treatment, heart failure (HF) and stroke; however, evidence of its clinical effectiveness remains mixed. While colchicine has shown prfomise in reducing recurrent cardiovascular events in stable CAD, its impact in postoperative AF prevention, acute coronary syndrome (ACS), HF, and stroke prevention is limited.